THE TRACE-COMPONENT TRAPPING EFFECT: EXPERIMENTAL EVIDENCE, THEORETICAL INTERPRETATION, AND GEOCHEMICAL APPLICATIONS - Urusov V.S.; Dudnikova V.B. (My University, 1998)
Experimental data indicating increase of crystal-melt (fluid) partition coefficients in the range of microconcentrations of trace elements are reviewed and analyzed in detail. This concentration dependence of partition coefficients has been referred to as either deviations from Henry’s law or the trace-component trapping effect.A critical review of a variety of models proposed to explain this phenomenon is also given. It is shown that the most reasonable and developed of these models relate changes in trace element partition coefficient at low concentrations to interactions between the trace element ions and metastable lattice defects (i.e., linear and planar defects) at low temperatures or intrinsic point defects of thermal origin at higher temperatures. The mechanism of interaction between trace element substituent atoms and intrinsic defects is considered in detail, with particular consideration given to the creation of pair associates, coupled substitutions, and the influence of other impurities on the trace element dissolution. The models developed are fit to the available experimental data to provide descriptions of the dependence of partition coefficients on composition and to estimate the concentrations and free energies of formation of the intrinsic defects (i.e., vacancies and interstitial atoms) in a matrix crystal. Some probable geochemical applications and manifestations of the trapping effect are discussed. This leads to the conclusion that there is an urgent need for further consideration of the problem.